Two-phase heat transfer in horizontal dimpled/protruded surface tubes with petal-shaped background patterns. (September 2019) - Sun, Zhi-chuan; Li, Wei; Ma, Xiang; Ma, Lian-Xiang; Yan, He
Highlights: Compared to the dimpled surface tube, the protruded surface tube has the smaller condensation HTC and larger evaporation HTC. Measured average HTC and pressure drop of the copper dimpled tube are higher than that of the stainless steel tube. The copper 1EHT series tubes exhibit satisfactory performance factors for both in-tube condensation and evaporation. Abstract: Experimental investigations were carried out to measure the average heat transfer coefficient and frictional pressure loss of R410A during condensation and evaporation in five newly-developed dimpled tubes and two smooth tubes. These dimpled tubes were called EHT series tubes enhanced by dimple or protrusion arrays and staggered petal-shaped background patterns on their inner surface. Tests were conducted at three condensation temperatures and two evaporation temperatures; over a mass flux range of 60–450 kg/(m 2 ·s); with an inlet vapor quality of 0.8/0.2 and outlet vapor quality of 0.2/0.8. Among the copper test tubes having the same outer diameter, the 1EHTa tube (dimpled surface tube) showed the highest condensing coefficient and pressure drop under the same test conditions. On the contrary, the superior evaporation heat transfer performance was given by the 1EHTb tube (protruded surface tube). In addition, the positive effects of small tube diameter and low saturation temperature on thermal performance have been confirmed. It was also observed that measured heat transfer coefficient and pressure drop of the copper 1EHTa tube were higher in comparison with the stainless steel one. The main reason could be the low thermal conductivity of stainless steel material. A comparison of heat transfer enhancement in these enhanced tubes has been done. Results indicated that both the copper 1EHTa and 1EHTb tubes provided the satisfactory surface thermal efficiency.